Pharmacodynamical evaluation of matrix type transdermal therapeutic systems containing captopril - (:unkn) unknown (Polish Pharmaceutical Society, 2015)
The objective of this study was to evaluate pharmacodynamical properties of transdermal therapeutic systems (TTS) containing captopril together with synthetic and pH independent polymers, Eudragit RL 100 and RS 100. Optimum formulation was chosen according to the results of our previous study regarding in vitro dissolution and ex vivo diffusion rate studies through excised human skin by using Franz Diffusion Cell. Control group, hypertension group (HT) and TTS containing captopril hypertension group (HT-CAP) were assessed for the pharmacodynamic activity of the study. Pharmacodynamic activity of transdermal patches containing captopril was evaluated in rats by the measurement of systolic blood pressure for 24 h with the use of the tail cuff method. Blood pressure, heart rate, body and heart weight, heart and body weight ratio were determined. Lactate dehydrogenase (LDH), creatinine phosphokinase (CPK), glutathione (GSH), malondialdehyde (MDA), myeloperoxidase (MPO) and Na+, K+-ATPase were measured in the serum of rats. Histopathological evaluation of the heart tissue was conducted in order to determine any tissue damage. Blood pressure values of the TTS containing captopril hypertension group were decreased significantly and became almost similar with the blood pressure values of the control group. These results indicated that matrix type transdermal patches prepared with Eudragit RL 100 and RS 100 polymers containing captopril can be considered as transdermal therapeutic systems for chronical treatment of hypertension and congestive heart failure. However, further in vivo pharmacokinetic studies should be performed in order to determine the blood level of the drug. © 2015, Polish Pharmaceutical Society. All rights reserved.
Keywords: Blood pressure; Captopril; Heart rate; Tail cuff; Transdermal therapeutic system